2008
DOI: 10.1038/sj.bjc.6604355
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of imatinib-free plasma levels and target genotype with efficacy and tolerability

Abstract: Imatinib has revolutionised the treatment of chronic myeloid leukaemia (CML) and gastrointestinal stromal tumours (GIST). Using a nonlinear mixed effects population model, individual estimates of pharmacokinetic parameters were derived and used to estimate imatinib exposure (area under the curve, AUC) in 58 patients. Plasma-free concentration was deduced from a model incorporating plasma levels of alpha 1 -acid glycoprotein. Associations between AUC (or clearance) and response or incidence of side effects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 51 publications
3
81
0
Order By: Relevance
“…Although a majority of nonresponding patients harbor mutations in the molecular drug targets (3,7,8), early resistance may also result from imatinib plasma levels that are below a minimal effective threshold level. Although not significant, patients with GIST not responding to imatinib treatment have shown lower imatinib plasma levels than responders (9,10). In addition, in a retrospective pharmacokinetic sidestudy of the pivotal phase II B2222 trial, a significant shorter time to progression was observed in patients that showed one-month imatinib steady-state trough levels below 1,100 ng/mL (10).…”
Section: Introductionmentioning
confidence: 99%
“…Although a majority of nonresponding patients harbor mutations in the molecular drug targets (3,7,8), early resistance may also result from imatinib plasma levels that are below a minimal effective threshold level. Although not significant, patients with GIST not responding to imatinib treatment have shown lower imatinib plasma levels than responders (9,10). In addition, in a retrospective pharmacokinetic sidestudy of the pivotal phase II B2222 trial, a significant shorter time to progression was observed in patients that showed one-month imatinib steady-state trough levels below 1,100 ng/mL (10).…”
Section: Introductionmentioning
confidence: 99%
“…A recent PK-PD analysis by Widmer et al, 33 using data from 58 patients, did not determine a straightforward correlation between free imatinib plasma exposure and clinical response, but further experiments may be warranted to clarify the role of variability in a 1 -acid glycoprotein activity on imatinib response.…”
Section: Differential Binding Of Imatinib By a 1 -Acid Glycoproteinmentioning
confidence: 99%
“…Although there is evidence of a link between imatinib exposure and toxicity in CML, 33 the correlation between plasma imatinib concentrations and adverse events may not be linear. In the IRIS trial, some adverse events were seen more frequently in patients with intermediate or lower plasma concentrations.…”
Section: Unusually Severe Adverse Reactionsmentioning
confidence: 99%
“…Although there is evidence of a link between imatinib plasma concentration and adverse events (AEs), 29 the characteristics of any such correlation are largely unknown. An analysis of data from the IRIS trial showed no major differences between the types and grades of AEs reported in patients in each of the trough plasma imatinib concentration quartiles.…”
Section: What Is the Relationship Between Imatinib Levels And Adversementioning
confidence: 99%